Clustered Regularly Interspaced Short Palindromic Repeat/CRISPR-Associated Protein and Its Utility All at Sea: Status, Challenges, and Prospects - Jiashun Li; Shuaishuai Wu; Kaidian Zhang; Xueqiong Sun; Wenwen Lin; Cong Wang; Senjie Lin (Microorganisms, 2024)
Initially discovered over 35 years ago in the bacterium Escherichia coli as a defense system against invasion of viral (or other exogenous) DNA into the genome, CRISPR/Cas has ushered in a new era of functional genetics and served as a versatile genetic tool in all branches of life science. CRISPR/Cas has revolutionized the methodology of gene knockout with simplicity and rapidity, but it is also powerful for gene knock-in and gene modification. In the field of marine biology and ecology, this tool has been instrumental in the functional characterization of ‘dark’ genes and the documentation of the functional differentiation of gene paralogs. Powerful as it is, challenges exist that have hindered the advances in functional genetics in some important lineages. This review examines the status of applications of CRISPR/Cas in marine research and assesses the prospect of quickly expanding the deployment of this powerful tool to address the myriad fundamental marine biology and biological oceanography questions.